Preoperative Iron Deficiency Is Associated With Increased Blood Transfusion in Infants Undergoing Cardiac Surgery - Gao, Peng; Wang, Xu; Zhang, Peiyao; Jin, Yu; Bai, Liting; Wang, Wenting; Li, Yixuan; Liu, Jinping (Frontiers in Cardiovascular Medicine, 2022)
Abstract Background: Iron deficiency (ID) is common in patients undergoing cardiac surgery, which is associated with adverse outcomes. However, the relevance of ID in congenital heart disease is still unclear. This study aimed to investigate the characteristics of preoperative ID and its association with clinical outcomes in infants undergoing cardiac surgery with cardiopulmonary bypass. Methods: In this retrospective study, 314 patients undergoing cardiac surgery were assigned into three groups according to their preoperative ID status. Absolute ID was defined by serum ferritin <12 ug/L, and functional ID was defined by serum ferritin level at 12-30 ug/L & transferrin saturation <20%. Baseline characteristics were compared between groups and multiple logistic regression was used to identify predictors for ID. The association between ID and clinical outcomes, including allogenic blood transfusion requirements, was also evaluated. Results: Among the 314 patients included, 32.48% were absolute ID and 28.66% were functional ID. Patients with absolute ID were more often of higher weight, cyanotic heart disease, and anemia. The presence of absolute ID was associated with an increase in postoperative blood transfusion (OR 1.837, 95% CI 1.016-3.321, p = 0.044). There was no significant difference in postoperative morbidity, mortality, and the length of hospital stay. Conclusions: Absolute ID was associated with preoperative anemia and cyanotic heart disease, and was an independent risk factor for postoperative blood transfusion. Further research should better explore the definition of ID and its impact on outcomes in pediatric cardiac surgery.